Some Characteristics of Polar Bears Killed during Conflicts with Humans in the Northwest Territories, 1976-86 - Stenhouse, G.B.; Lee, L.J.; Poole, K.G. (ARCTIC, 1988)
We examined 265 cases where polar bears were killed in the Northwest Territories as a result of bear-human encounters between 1 July 1976 and 30 June 1986. Age and sex of the bears, time of year and general circumstances of the cases were characterized. Subadult animals constituted 53% of the aged sample, and males accounted for 70% of the sexed bears. Subadult males represented 40% of known age and sex bears. Problem kills occurred throughout the year but were most frequent in the ice-free season (August-November). In 222 cases where circumstances surrounding the death were known, 63% were associated with Inuit on the land, 18% with settlements, 15% were industrial sites and 4% with research activities. Most problem kills (87%) were not included in the quota harvest. This mortality in excess of the quota may adversely affect some populations. Therefore, wherever possible we encourage the inclusion of problem bears on community quotas.Key words: polar bear (Ursus maritimus), problem bears, bear-human encounters, Arctic, Northwest Territories Mots clés: ours polaire (Ursus maririmus), ours-problèmes, rencontres entre l’homme et l’ours, Arctique, Territoires du Nord-Ouest